13.9k views
5 votes
F(x) = 2x² +2
g(x) =-3x-3
Find f(-2) and g(2).

User Findango
by
5.3k points

2 Answers

0 votes

Answer:


f( - 2) = 10 \\ g(2) = - 9

Explanation:


f(x) = 2x { }^(2) + 2 \\ f( - 2) = 2( - 2) {}^(2) + 2 \\ = 10 \\ \\ g(x) = - 3x - 3 \\ g(2) = - 3(2) - 3 \\ = - 9

User Pkh
by
5.2k points
4 votes

Answer:

Explanation:

f(-2) = 2(-2)^2 + 2 = 2(4) + 2 = 8 + 2 =10

g(2) = -3(2) - 3 = -6 -3 = -9

User Dashrath Mundkar
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.